Library Security Management: An Introduction - Nielsen, Erland Kolding (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
During the last week of January 2001, the Royal Library suffered serious thefts in both its special reading rooms for maps and for manuscripts and rare books. Precious maps were removed from folio editions and smuggled out by a thief who was something of a magician. For years the Royal Library has been one of the most effectively secured buildings housing cultural assets in Denmark. Nevertheless, this incident happened and apparently could happen. The thefts were discovered the same day, but the thief had become suspicious and did not reappear over the next few days as expected. However, because the theft had been filmed on security cameras in the reading room, we had very good photographs of the thief. After days of hard work we were able to discover from the security film how the theft had been carried out and how the items had been smuggled out of the reading room. On the second day after the incident, I warned my fellow directors in the Nordic national libraries and in a number of university libraries with historical collections. Nevertheless, the following week the thief or his accomplice visited Helsinki University Library, and later we discovered that they had been in the Royal Library in The Hague at almost the same time, as well as some months earlier, and in the Royal Library in Stockholm on numerous occasions from the autumn of 2000 onwards.